Artificial Intelligence in Driving Cars – A Review Paper (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The fundamental plan behind the project is to develop an automatic automotive  that may sense its setting and move while not human input. This paper proposes  automotive automation, that is accomplished by recognizing the road, signals,  obstacles, stop signs, responding and creating decisions, like ever-changing  the course of the vehicle, stopping red signals, stopping signs, and moving on  inexperienced signals mistreatment Neural Network. Self-driving automotive  processes input, tracks a track and sends directions to the actuators that  management acceleration, braking, and steering. The software tracks traffic by  means that of hard-coded rules, preventive algorithms, prognosticative modeling,  and “smart” discrimination on objects, serving to the computer code to follow  rules on transport
Keywords: Self-driving; Neural Network; Actuators; predictive modeling; preventive algorithms; smart discrimination